Can area measurement error explain the inverse farm size productivity relationship? - Stein Holden; Monica Fisher (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2013)
The existence of an inverse relationship (IR) between farm size and productivity in tropical agriculture remains a debated issue with policy relevance. Poor agricultural statistical data, including data on farm sizes and farm plot sizes that typically are self-reported by farmers, can lead to biased results and wrong policy conclusions. This study combines self-reported and GPS-measured farm plot and farm sizes to assess how measurement error affects the IR using three rounds of farm plot and household data from Malawi. The results show that measurement error covers up more than 60% of the IR for the total sample but leads to an upward bias in the IR on farms less than one ha. Land and labor market imperfections in combination with food self-sufficiency motives appear to explain most of the IR and lead to a strong IR on farms below one ha.
Keywords: J43; O13; Q12; 330; Inverse farm size – productivity relationship; Measurement error; Land and labor market imperfections; Land quality; Malawi